Editorial - Kypriotis, Eugenia (Open Schools Journal for Open Science, 2020)
This is the second issue of the Open Schools Journal for Open Science created an interest in the education community in Greece and in other European countries. The organisers of the Student Conference on Research and Science that took place in Greece in 2018 after the success of presenting the conference’ findings of their first conference expressed again their interest to present the valuable work that has been presented during the 2nd Student Conference on Research and Science. This is the first of a series of four issues which will be published until July 2020 and it contains 22 articles written by students from across Greece in collaboration with their teachers/mentors. Have a look at the welcome note from the programme committee of the conference. All articles in this special issue are written in Greek.